2011
DOI: 10.1124/jpet.111.179556
|View full text |Cite
|
Sign up to set email alerts
|

A Study Comparing the Antisecretory Effect of TAK-438, a Novel Potassium-Competitive Acid Blocker, with Lansoprazole in Animals

Abstract: Proton pump inhibitors (PPIs) are widely used for the treatment of acid-related diseases. However, several medical needs such as suppression of night-time acid secretion and rapid symptom relief remain unmet. In this study, we investigated the effects of 1-[5-(2-fluorophenyl)-1-(pyridin-3-ylsulfonyl)-1H-pyrrol-3-yl]-Nmethylmethanamine monofumarate (TAK-438), a novel potassium-competitive acid blocker, on acid secretion in rats and dogs under various conditions, in comparison with the PPI, to characterize the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
112
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(114 citation statements)
references
References 34 publications
(45 reference statements)
2
112
0
Order By: Relevance
“…Compared with LPZ, VPZ exhibits more potent and sustained acid-inhibitory effects, and induction of greater increases in gastric pH, consistent with the observation that VPZ accumulates to higher concentrations and is cleared at a slower rate from gastric glands (16,17). In addition, the intragastric pH following VPZ treatment (pH 5.2) has been identified to be significantly higher than that following esomeprazole treatment (pH 3.0) on day 1 of therapy (18).…”
Section: Eradication Rate % (N) -------------------------------------supporting
confidence: 74%
“…Compared with LPZ, VPZ exhibits more potent and sustained acid-inhibitory effects, and induction of greater increases in gastric pH, consistent with the observation that VPZ accumulates to higher concentrations and is cleared at a slower rate from gastric glands (16,17). In addition, the intragastric pH following VPZ treatment (pH 5.2) has been identified to be significantly higher than that following esomeprazole treatment (pH 3.0) on day 1 of therapy (18).…”
Section: Eradication Rate % (N) -------------------------------------supporting
confidence: 74%
“…Vonoprazan is one of the new class of acid-suppressing agents that may be used as an alternative to PPIs as blocker of gastric hydrogen-potassium adenosine triphosphatase, which inhibits the critical final step in gastric acid secretion by reversing K+-competitive ionic binding. The pharmaceutical advantages of P-CAB over PPIs include more rapid, stronger and longer-lasting inhibition of gastric acid secretion after administration [7,15,16]. For the treatment of peptic ulcers, Miwa et al reported that a 20 mg dose of vonoprazan had a similar tolerability profile as a 30 mg dose of lansoprazole, and was not inferior to lansoprazole with respect to gastric ulcer healing [17].…”
Section: Discussionmentioning
confidence: 99%
“…In comparison with PPIs, PCABs bind to the proton pump continuously in gastric parietal cells to reduce gastric acid secretion without requiring activation or being deactivated by the gastric acid. Furthermore, it was reported that PCABs are not affected by genetic polymorphisms of CYP2C19 (23,24). In patients with GERD whose gastric acid secretion was not suppressed sufficiently well by the administration of a PPI, it may be possible to control the secretion further by administering a PCAB.…”
Section: Discussionmentioning
confidence: 99%